Gingival recession of mandibular incisor post-orthodontic treatment: a systematic review - Rizky Fathhiyah Wahab; Sri Oktawati; Surijana Mappangara (Makassar Dental Journal, 2020)
Objective: To evaluate the effect of orthodontic movement on gingival recession of mandibular incisor. Method: Pubmed and Wileyonline searches were conducted to identify articles published in dental journals until November 2018 focusing on relationship betweengingival recession of mandibular incisors after orthodontic treatment. Manual searches of published full-text articles and related reviews were performed afterwards. Result: All articles were 103 selected for full-text review. A total 4 studies were selected for inclusion, with 462 subjects. All of the studies showed the mean increase in clinical crown height of the lower incisors was not statistically significant.Conclusion: It was concluded that orthodontic treatment did not affect the developmental of gingival recession on mandibular incisors.